ON THE ISSUE OF SUBSTANTIATION OF THE METHOD FOR DETERMINING ROLLING FRICTION COEFFICIENTS AND THE DEVICE FOR ITS IMPLEMENTATION (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The paper considers the issue of substantiating the method for determining the coefficients of rolling friction and the device for its implementation. The methods for determining the coefficients of static, sliding and rolling friction are analyzed. The relevance of the paper lies in the fact that the methods for determining the coefficients of static friction are based either on determining the friction force using dynamometers and on this basis determining the coefficient of static friction, or on the use of inclined surfaces. The aim and objective of the research is to substantiate the method for determining the coefficients of rolling friction and the device for its implementation. The paper applies theoretical and computational-experimental methods based on the provisions of theoretical mechanics and methods of statistical processing of experimental data. Millet, rapeseed, pea and soybean seeds were used to study the angles and coefficients of friction. It is shown that the proposed devices for determining the coefficients of rolling friction of individual small particles, for example grains, are complex in design and are not produced by industry. It is shown that friction plays a significant role both in our lives and in many branches of technology. It is present in everyday actions, in the use of transport and other means of transportation, where friction is necessary to prevent slipping and ensure safety. It is noted that friction can also be negative, for example, in various mechanisms when the movement of bodies relative to each other is difficult, and sometimes the movement itself. The paper substantiates the method for determining the coefficients of rolling friction, in which the essence of the process of determining the rolling coefficient of a particle consists in fixing the angle of inclination of the inclined plane on which the particle is located, with its gradual increase until the beginning of the particle's movement, determining the tangent of this angle and multiplying it by the radius of the particle.
Keywords: friction; coefficient; method; rolling; justification; device